Initiation of a ZAKα-dependent ribotoxic stress response by the innate immunity endoribonuclease RNase L - Jiajia Xi; Goda Snieckute; José Francisco Martı́nez; Frederic Schrøder Arendrup; Abhishek Asthana; Christina Gaughan; Anders H. Lund; Simon Bekker‐Jensen; Robert H. Silverman (2024)
RNase L is an endoribonuclease of higher vertebrates that functions in antiviral innate immunity. Interferons induce oligoadenylate synthetase enzymes that sense double-stranded RNA of viral origin leading to the synthesis of 2′,5′-oligoadenylate (2-5A) activators of RNase L. However, it is unknown precisely how RNase L remodels the host cell transcriptome. To isolate effects of RNase L from other effects of double-stranded RNA or virus, 2-5A is directly introduced into cells. Here, we report that RNase L activation by 2-5A causes a ribotoxic stress response involving the MAP kinase kinase kinase (MAP3K) ZAKα, MAP2Ks, and the stress-activated protein kinases JNK and p38α. RNase L activation profoundly alters the transcriptome by widespread depletion of mRNAs associated with different cellular functions but also by JNK/p38α-stimulated induction of inflammatory genes. These results show that the 2-5A/RNase L system triggers a protein kinase cascade leading to proinflammatory signaling and apoptosis.